Phylogenetic analysis of flatfish (order pleuronectiformes) based on mitochondrial 16s rDNA sequences - Pardo, Belén G.; Machordom, Annie; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP]; Azevedo, Marisa F.C. [UNESP]; Bañon, Rafael; Sánchez, Laura; Martínez, Paulino (Editorial CSIC, 2005)
The phylogenetic relationships of the order Pleuronectiformes are controversial and at some crucial points remain unresolved. To date most phylogenetic studies on this order have been based on morpho-anatomical criteria, whereas only a few sequence comparisons based studies have been reported. In the present study, the phylogenetic relationships of 30 flatfish species pertaining to seven different families were examined by sequence analysis of the first half of the 16S mitochondrial DNA gene. The results obtained did not support percoids as the sister group of pleuronectiforms. The monophyletic origin of most families analyzed, Soleidae, Scophthalmidae, Achiridae, Pleuronectidae and Bothidae, was strongly supported, except for Paralichthyidae which was clearly subdivided into two groups, one of them associated with high confidence to Pleuronectidae. The analysis of the 16S rRNA gene also suggested the monophyly of Pleuronectiforms as the most probable hypothesis and consistently supported some major interfamily groupings.
Keywords: 16S mtDNA; Phylogenetic analysis; Pleuronectiformes; flatfish; mitochondrial DNA; phylogenetics; Achiridae; Bothidae; Paralichthyidae; Pleuronectidae; Scophthalmidae; Soleidae